Ecology and diversity of Cortinarius species (Agaricales, Basidiomycota) associated with Quercus ilex L. in the Mediterranean area of Liguria (North-western Italy) - Zotti, M; Ambrosio, E; Di Piazza, S; Bidaud, A; Boccardo, F; Pavarino, M; Mariotti, M G; Vizzini, A (Plant Biosystems - An International Journal Dealing with all Aspects of Plant Biology, 2014)
Cortinarius is one of the most widespread macrofungal genera. Although Mediterranean basin is considered a biodiversity hotspot, very few studies have addressed the presence and importance of Cortinarius species in such area. Surveys were carried out in Liguria (NW Italy) in different habitats characterized by the presence of Quercus ilex. Altogether 67 taxa were observed: 49 of them are new records for Liguria while 23 represent new records for Italy. In addition, we report the distinguishing characters and ecological traits of the species which are also rare in Europe.
doi: 10.1080/11263504.2013.877538
Keywords: Agaricomycetes; Biodiversity; conservation; Cortinariaceae; holm-oak; Macrofungi

Influence of pollen emission and weather-related factors on variations in holm-oak (Quercus ilex subsp. ballota) acorn production - García-Mozo, H.; Gómez-Casero, M.T. T; Dominguez, E.; Galan, C. (Environmental and Experimental Botany, 2007)
In Iberian Mediterranean ecosystems holm-oak acorn production is of vital ecological and economic importance. Economically these fruits are the major component in the feeding systems of high-quality domestic pigs. As in most Quercus species, the chief feature of holm-oak acorn production is its high variability among individuals and years. Many hypotheses have been put forward to explain these ﬂuctuations, but the variables inﬂuencing this alternating behavior remain unknown. From 1998 to 2003 we studied ﬂoral phenology, fruit production, fruit size, airborne pollen emission and meteorology in a holm-oak natural area of South Spain. The results obtained by using a Principal Components Factorial Analysis indicated that pollen emission, up to the day where maximum pollen data are recorded, was the most important factor determining ﬁnal acorn harvest. With regard to the inﬂuence of the weather, temperature, relative humidity and rainfall of January, March and September were the most inﬂuencing variables. Our results support the “wind pollination” hypothesis proposed by other authors in some North-American Quercus studies. Integration of aerobiological, ﬁeld phenological and meteorological data could represent an important step forward in forest fruit production research.
Keywords: acorn; Aerobiology; ballota; holm-oak; oak forest; Phenology; pollen; quercus ilex subsp; quercus ilex subsp. ballota

Influence of pollen emission and weather-related factors on variations in holm-oak (Quercus ilex subsp. ballota) acorn production - García-Mozo, H.; Gómez-Casero, M. T. T.; Dominguez, E.; Galan, C. (Environmental and Experimental Botany, 2007)
In Iberian Mediterranean ecosystems holm-oak acorn production is of vital ecological and economic importance. Economically these fruits are the major component in the feeding systems of high-quality domestic pigs. As in most Quercus species, the chief feature of holm-oak acorn production is its high variability among individuals and years. Many hypotheses have been put forward to explain these ﬂuctuations, but the variables inﬂuencing this alternating behavior remain unknown. From 1998 to 2003 we studied ﬂoral phenology, fruit production, fruit size, airborne pollen emission and meteorology in a holm-oak natural area of South Spain. The results obtained by using a Principal Components Factorial Analysis indicated that pollen emission, up to the day where maximum pollen data are recorded, was the most important factor determining ﬁnal acorn harvest. With regard to the inﬂuence of the weather, temperature, relative humidity and rainfall of January, March and September were the most inﬂuencing variables. Our results support the “wind pollination” hypothesis proposed by other authors in some North-American Quercus studies. Integration of aerobiological, ﬁeld phenological and meteorological data could represent an important step forward in forest fruit production research.
Keywords: acorn; Aerobiology; ballota; holm-oak; oak forest; Phenology; pollen; quercus ilex subsp; quercus ilex subsp. ballota

Phytoclimatic characterization of holm-oak provenances (Quercus ilex L.) in the Central-Northern Iberian Peninsula - Garcia Lopez, J. M.; Gonzalo Jimenez, J.; ALLUÉ CAMACHO, C. (Forest Systems, 2002)
This paper presents some contributions to the phytoclimatic characterization of stands of holm-oak (Quercus ilex. L.) in the centre-north of the Iberian Peninsula and the testing of a method of phytoclimatic homologation applicable to the characterization of provenances of the species. For the phytoclimatic characterization, 432 sampling points in the Province of Burgos were considered, corresponding to the centres of cartographic tessellae of actual vegetation in which holm-oak was the principle species of the forest (18,965 ha). The phytoclimatic diagnosis followed the phytoclimatic models of Allué-Andrade. Phytoclimatic territorial models were constructed in digital format on the basis of preliminary territorial factorial estimations, which were used to determine phytoclimatic terns. Based on the establishment of phytoclimatic ambits for the existence of holm-oak stands in Burgos and stratification in accordance with the five phytoclimatic subtypes (VI(IV)1, VI(IV)2, VI(VII), VI(V) and VI), phytoclimatic homologation was performed in three phases of increasing strictness, all based on a comparison of phytoclimatic terns derived from the general and specific phytoclimatic systems. In the strictest homologation, an adequate and territorially compact degree of discrimination was achieved for 2.622.500 ha (Quercus ilex subsp. ballota) and 116.00 ha (Quercus ilex subsp. ilex) in the centre-north of the Iberian Peninsula. The marked edaphic azonality of the species was an important factor in the interpretation of the results.
Keywords: holm-oak; homologation; phytoclimatology; provenances; Quercus ilex L. subsp. ballota (Desf.) Samp.; Quercus ilex L. subsp. ilex

Phytoclimatic characterization of holm-oak provenances (Quercus ilex L.) in the Central-Northern Iberian Peninsula - Garcia Lopez, J M; Gonzalo Jimenez, J; ALLUÉ CAMACHO, C (Forest Systems, 2002)
This paper presents some contributions to the phytoclimatic characterization of stands of holm-oak (Quercus ilex. L.) in the centre-north of the Iberian Peninsula and the testing of a method of phytoclimatic homologation applicable to the characterization of provenances of the species. For the phytoclimatic characterization, 432 sampling points in the Province of Burgos were considered, corresponding to the centres of cartographic tessellae of actual vegetation in which holm-oak was the principle species of the forest (18,965 ha). The phytoclimatic diagnosis followed the phytoclimatic models of Allué-Andrade. Phytoclimatic territorial models were constructed in digital format on the basis of preliminary territorial factorial estimations, which were used to determine phytoclimatic terns. Based on the establishment of phytoclimatic ambits for the existence of holm-oak stands in Burgos and stratification in accordance with the five phytoclimatic subtypes (VI(IV)1, VI(IV)2, VI(VII), VI(V) and VI), phytoclimatic homologation was performed in three phases of increasing strictness, all based on a comparison of phytoclimatic terns derived from the general and specific phytoclimatic systems. In the strictest homologation, an adequate and territorially compact degree of discrimination was achieved for 2.622.500 ha (Quercus ilex subsp. ballota) and 116.00 ha (Quercus ilex subsp. ilex) in the centre-north of the Iberian Peninsula. The marked edaphic azonality of the species was an important factor in the interpretation of the results.
Keywords: holm-oak; homologation; phytoclimatology; provenances; Quercus ilex L. subsp. ballota (Desf.) Samp.; Quercus ilex L. subsp. ilex

Gas exchange measurements and an indirect estimate of primary production in a holm-oak ecosystem - Manes, F; Vitale, M; Feoli, E; Scimone, M; Canfora, E (FRESENIUS ENVIRONMENTAL BULLETIN, 1998)
An original and simple primary production model is presented. Annual trends of the daily average values of net photosynthesis and leaf transpiration for helm oak are showed. Moreover, primary production data were obtained. To validate the model, an evaluation between estimated results and field measurements was performed, obtaining a strong correspondence.
Citation
Keywords: holm-oak; photosynthesis; plant simulation model; primary production; Transpiration

Fenofases florales en quercus rotundifolia lam. - Vázquez, F M (II Congreso Forestal Español, 1997)
In this work the floral stages are introduced that it is happened in the masculine and feminine flowering of the holm-oak (Quercus rotundifolia Lam.). In each described stages they incorporate data on the floral morphology: state of development that it reach the catkins, the floral group and the tlowers. Also data of the receptive state in the are inserted feminine tlowers and ripening and viability grade of the grain of ponen and ovule. Finally is represented in a graphic each one of the described stage. K.W.:
Keywords: flowering; holm-oak; Ovule; pollen; Quercus rotundifolia; reproduction; Stages

Actividad espacio-temporal de Polietes meridionalis Peris & Llórente , 1963 ( Díptera : Muscidae ) en un ecosistema de encinar * - Rojo, S; Marcos-garcía, M A (Boletín de Sanidad Vegetal Plagas, 1995)
Some aspects of the biology of Polietes meridionalis Peris & Llórente 63 have been analysed in a holm-oak ecosystem (dehesa) located in the Tberian Mediterranean área. The specimens were caught with pit-fall traps baited with cattle dung, placed according to habitat gradient. They were collected at dífferent hourly periods to fix a distribution model in space and time and its variation during the year.
Keywords: coprophagous diptera; Diptera; holm-oak; Muscidae; Polietes meridionalis; space-temporal distribution

RUPTURE IN A COLLEMBOLA COMMUNITY STRUCTURE FROM A QUERCUS-ROTUNDIFOLIA LAM FOREST DUE TO THE REAFFORESTATION WITH EUCALYPTUS-GLOBULUS LABILL - SOUSA, J. P.; DAGAMA, M. M. (EUROPEAN JOURNAL OF SOIL BIOLOGY, 1994)
Here we compare Collembola populations from a Quercus rotundifolia forest and an Eucalyptus globulus plantation. The overall analysis of data (using both diversity and similarity measures) have shown clear signs of rupture on the structure of collembola populations, with the fauna associated with the Quercus stand being richer (in exclusive and preferential species) and more abundant than the one connected with the Eucalyptus. Data also reflects the faunal stratification between organic and mineral horizons, with the majority of species being associated with upper soil layers in detriment of mineral horizon. These disruptions may be related to profound alterations of habitat characteristics, particularly the frequent removal of shrub vegetation and leaf layer, result of the forestry practices connected with the preparations and management of the eucalyptus plantation.
The following values have no corresponding Zotero field: pub-location: DEPT UNIV PROFESSIONNEL REVUES SCIENTIFIQUES TECHNIQUE 11 RUE GOSSIN, F-92543 MONTROUGE, FRANCE publisher: GAUTHIER-VILLARS
Keywords: Collembola; EUCALYPTUS; holm-oak; REAFFORESTATION

RUPTURE IN A COLLEMBOLA COMMUNITY STRUCTURE FROM A QUERCUS-ROTUNDIFOLIA LAM FOREST DUE TO THE REAFFORESTATION WITH EUCALYPTUS-GLOBULUS LABILL - Sousa, J P; DaGama, M M (EUROPEAN JOURNAL OF SOIL BIOLOGY, 1994)
Here we compare Collembola populations from a Quercus rotundifolia forest and an Eucalyptus globulus plantation. The overall analysis of data (using both diversity and similarity measures) have shown clear signs of rupture on the structure of collembola populations, with the fauna associated with the Quercus stand being richer (in exclusive and preferential species) and more abundant than the one connected with the Eucalyptus. Data also reflects the faunal stratification between organic and mineral horizons, with the majority of species being associated with upper soil layers in detriment of mineral horizon. These disruptions may be related to profound alterations of habitat characteristics, particularly the frequent removal of shrub vegetation and leaf layer, result of the forestry practices connected with the preparations and management of the eucalyptus plantation.
Keywords: Collembola; EUCALYPTUS; holm-oak; REAFFORESTATION

CARACTERIZACION ESTRUCTURAL DE LOS ENCINARES DE CATALUÑA Marc - Gracia, Marc; Retana, Javier; Espelta, Josep Maria; Gené, Caries (Congreso Forestal Español, Lourizán - Pontevedra. 1993, 1993)
In this paper, a characterization of structure of holm-oak forests in the Northeastem Iberian Peninsula is proposed. The study is based on different features of these forests, both at the stand and at the individuallevel.
Keywords: Basal area; density of stems; Forest structure; holm-oak; Quercus ilex; size distri bu ti on

Different vulnerabilities of Quercus ilex L. to freeze- and summer drought-induced xylem embolism: an ecological interpretation - LO GULLO, M A; Salleo, S (Plant, Cell & Environment, 1993)
Quercus ilex L. growing in the southern Mediterranean Basin region is exposed to xylem embolism induced by both winter freezing and summer drought. The distribution of the species in Sicily could be explained in terms of the different vulnerability to embolism of its xylem conduits. Naturally occurring climatic conditions were simulated by: (1) maintaining plants for 3h at ambient temperatures of 0, -1.5, -2.5, -5.0 and -11°C; and (2) allowing plants to dry out to ratios of their minimum diurnal leaf water potentials (Ψ1) to that at the turgor loss point (Ψtlp) of 0.6, 0.9, 1.05, 1.20 and 1.33. The loss of hydraulic conductivity of one-year-old twigs reached 40% at -1.5°C and at Ψ1/ΨtlP= 1.05. Recovery from these strains was almost complete 24 h after the release of thermal stress or after one irrigation, respectively. More severe stresses reduced recovery consistently. The percentages of xylem conduits embolized following application of the two stresses, were positively related to xylem conduit diameter. The capability of the xylem conduits to recover from stress was positively related to the conduit diameter in plants subjected to summer drought, but not in the plants subjected to winter freezing stress. The ecological significance of the different vulnerabilities to embolism of xylem conduits under naturally occurring climatic conditions is discussed.
Keywords: conduit diameter; Fagaceae; holm-oak; hydraulic conductivity; Quercus ilex L.; summer drought; winter freezing; xylem embolism

Different vulnerabilities of Quercus ilex L. to freeze- and summer drought-induced xylem embolism: an ecological interpretation - Lo Gullo, M. A.; Salleo, S. (Plant, Cell & Environment, 1993)
Quercus ilex L. growing in the southern Mediterranean Basin region is exposed to xylem embolism induced by both winter freezing and summer drought. The distribution of the species in Sicily could be explained in terms of the different vulnerability to embolism of its xylem conduits. Naturally occurring climatic conditions were simulated by: (1) maintaining plants for 3h at ambient temperatures of 0, -1.5, -2.5, -5.0 and -11°C; and (2) allowing plants to dry out to ratios of their minimum diurnal leaf water potentials (Ψ1) to that at the turgor loss point (Ψtlp) of 0.6, 0.9, 1.05, 1.20 and 1.33. The loss of hydraulic conductivity of one-year-old twigs reached 40% at -1.5°C and at Ψ1/ΨtlP= 1.05. Recovery from these strains was almost complete 24 h after the release of thermal stress or after one irrigation, respectively. More severe stresses reduced recovery consistently. The percentages of xylem conduits embolized following application of the two stresses, were positively related to xylem conduit diameter. The capability of the xylem conduits to recover from stress was positively related to the conduit diameter in plants subjected to summer drought, but not in the plants subjected to winter freezing stress. The ecological significance of the different vulnerabilities to embolism of xylem conduits under naturally occurring climatic conditions is discussed.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: conduit diameter; Fagaceae; holm-oak; hydraulic conductivity; Quercus ilex L.; summer drought; winter freezing; xylem embolism

Evidence for hybridization between sympatric holm-oak and cork-oak in Spain based on diagnostic enzyme markers - Elena-Rossello, J. A.; Lumaret, R.; Cabrera, E.; Michaud, H. (Plant Ecology, 1992)
Hybridization has been detected in mixed populations of juvenile cork-oak and holm-oak individuals using three diagnostic enzyme loci coding for esterases, leucine amino peptidases and acid phosphatases respectively. Among the 35 studied individuals, 29, 5 and 1 were identified as holm-oak, cork-oak and hybrid respectively. Such diagnostic markers are likely to be useful to detect and remove hybrids at the juvenile stage in areas where the holm-oak is grown for acorn production and the cork-oak is cultivated for cork. This is necessary since hybrid adults produce neither cork nor acorns of high quality.
Keywords: cork-oak; enzyme markers; holm-oak; Hybridization; Quercus

Litterfall as a measure of primary production in Mediterranean holm-oak forest - Bellot, J.; Sánchez, J. R.; Lledó, M. J.; Martínez, P.; Escarré, A. (Plant Ecology, 1992)
In this paper we discuss the use of litterfall as a method to measure primary production and its between year relation to climatic fluctuation. Seven years of study in a mediterranean holm-oak forest showed a moderate inter-annual variability of litterfall (C.V. 11°;), while the annual variability of the actual or evapotranspiration was three times higher (C.V. 30/o). Furthermore, the inter- and intra-annual vari- ability of nutrient content in the various fractions are presented in relation to water availability. Monthly and seasonal variability was higher than the annual variability for all analyzed elements.
Keywords: holm-oak; litterfall; litterfall nutrient contents; mediterranean forest; primary production; Quercus ilex; temporal variability

Influence of particle size and pyrolysis conditions on yield, density and some textural parameters of chars prepared from holm-oak wood - Valenzuela-Calahorro, C; Bernalte-Garcia, A; Gómez-Serrano, V; Bernalte-García, Ma.J. (Journal of Analytical and Applied Pyrolysis, 1987)
Chars were prepared from holm-oak wood (Quercus ilex) using sawdust, cubes (20 × 20 × 20 mm) and octagonal prisms (20 × 20 × 80 mm) by heating in nitrogen under dynamic (sawdust and cubes) and isothermal (sawdust and prisms) conditions to different final temperatures. The yield of char production depends on the wood particle size, heating rate and final temperature. The density of the chars as measured by helium displacement, ϱHe (g/cm3), is influenced by the wood particle size and heating conditions. Chars prepared from holm-oak wood are essentially microporous solids. The apparent surface area and the micropore volume increase only slightly up to the treatment temperature of 500°C, increase greatly up to 800°C and decrease at higher temperatures.
Keywords: biomass; chars; holm-oak; pyrolysis; wood.